The validity of the Big Five personality traits for job performance: Meta‐analyses of South African studies. (September 2017) - van Aarde, Ninette; Meiring, Deon; Wiernik, Brenton M.
Abstract : Previous meta‐analyses have established the Big Five personality traits as important predictors of job performance around the globe. This study extends the international generalizability of Big Five criterion‐related validity through systematic review and meta‐analyses of personality–performance research conducted in South Africa. We meta‐analyzed data from 33 studies and 6, 782 individuals to estimate validities of Big Five traits for various job performance criteria. Results showed that the Big Five traits have similar validity for job performance criteria as found in other cultural contexts. Conscientiousness was the strongest predictor across performance criteria, while other traits showed validity for specific criteria or subsamples. Results demonstrate the importance of psychometric meta‐analysis for building cumulative knowledge and support applied use of personality assessments in South Africa. Consistency of the results of this study with those of previous meta‐analyses in other national contexts supports the argument that personality–performance relations are a cultural universal.